Status, ecology and life history of harbour porpoise (Phocoena phocoena), in Danish waters - Lockyer, Christina; Kinze, Carl (NAMMCO Scientific Publications, 2003)
A review of historical harbour porpoise catches in Danish waters, together with current distribution, are provided. Most information on distribution is derived from historical catch data with a total of about 100,000 animals taken in Little Belt alone and 40,000 from Isefjord area during the 19th century. Recent sightings surveys and tagging indicate extensive movements of animals within and between Inner Danish Waters and the Skagerrak / North Sea. Biological information is reviewed for the region, drawing on directed catches, bycatches and strandings from a databasecomprising nearly 1,900 records from 1834 through 1998. Diet, parasites, pollutants, biological parameters (age and reproduction) and body condition are reported, focusing mainly on the period 1996-98 when comprehensive data were collected. In 1980s samples, gadoids were the most important prey items (found in 62% of stomachs) followed by clupeoids (35%), gobiids (30%), and ammodytids (30%). Some dietary differences were observed between North Sea and Inner Danish waters. Pollutant analyses indicated a decline in sumDDT concentrations yet an increase in sumPCB and HCH levels in Danish porpoises, with comparatively higher levels here than in Baltic and Norwegian waters. Heavy metal concentrations appear higher than in Baltic porpoises. Biological parameters indicate a longevity of up to 23 years in both sexes but with fewer than 5% living beyond 12 years. Sexual maturity occurred at slightly over age 3 years in both females and males, with corresponding lengths of about 135 cm in males and 143 cm in females. The dataindicate a size range at birth of 65 - 75 cm (weight 4.5 – 6.7 kg), with a minimum of 60 cm and 3.4 kg, and a likely gestation time of 10 months. Conception most likely occurs during August, with peak births in June. Directed catches comprised adult animals whereas bycaught and stranded porpoises comprised predominantly juveniles. In data from all sources, males outnumbered females. Directed catches occurred in winter months, strandings year-round with a peak in late summer, and bycatches year-round with most in September and the later part of the year.